Characterization of Subtype H6 Avian Influenza A Viruses Isolated From Wild Birds in Poyang Lake, China - Wan, Zhimin; Kan, Qiuqi; Zhao, Zhehong; Shao, Hongxia; Deliberto, Thomas J.; Wan, Xiu-Feng; Qin, Aijian; Ye, Jianqiang (Frontiers in Veterinary Science, 2021)
Subtype H6 avian influenza A viruses (IAVs) are enzootic and genetically diverse in both domestic poultry and wild waterfowl, and some H6 viruses have caused infections in pigs and humans. Thus, it is important to understand the genetic diversity of H6 IAVs in birds and their potential in infecting humans. Compared with that in domestic poultry, the genetic diversity of H6 viruses in wild birds in China have not been well understood. In this study, five H6 viruses were isolated from wild birds in Poyang Lake, China, and genomic analyses showed that these isolates are clustered into four genotypes with reassortments among avian IAVs from domestic poultry and wild birds and those from Eurasia and North America. The five isolates had distinct phenotypes in growth kinetics analyses with mammalian cells lines and in mouse challenge experiments. Two of these H6 isolates, from the Eurasian teal, replicated effectively in the mouse lung without prior adaptation. In summary, this study suggested that mammalian viral replication efficiency phenotypic variants exist among genetically diverse H6 IAVs in wild birds, and that both intra- and inter-continental movements of IAVs through wild bird migration facilitates the emergence of genetically and phenotypically diverse H6 IAVs. Continued surveillance to monitor the diversities of H6 IAVs in wild birds, especially those unrepresentative regions such as China, is necessary to increase our understanding of the natural history of IAVs.